Chinese Lexical Semantics 13th Workshop, CLSW 2012, Wuhan, China, July 6-8, 2012, Revised Selected Papers - Ji, Donghong.; Ji, Donghong.; Xiao, Guozheng.; Xiao, Guozheng. (Lecture Notes in Artificial Intelligence ;, 2013)
This book constitutes carefully reviewed and revised selected papers from the 13th Chinese Lexical Semantics Workshop, CLSW 2012, held in Wuhan, China, in July 2012. The 67 full papers and 17 short papers presented in this volume were carefully reviewed and selected from 169 submissions. They are organized in topical sections named: applications on natural language processing; corpus linguistics; lexical computation; lexical resources; lexical semantics; new methods for lexical semantics; and other topics.